GAMLSS: A distributional regression approach. (June 2018) - Stasinopoulos, Mikis D; Rigby, Robert A; Bastiani, Fernanda De
Abstract: A tutorial of the generalized additive models for location, scale and shape (GAMLSS) is given here using two examples. GAMLSS is a general framework for performing regression analysis where not only the location (e.g., the mean) of the distribution but also the scale and shape of the distribution can be modelled by explanatory variables.